Structural Discrimination in Online Defamation Enforcement: A Hybrid Analysis of Malaysian Criminal Law and Islamic Jurisprudence - Abdul Basir Mohamad; Nurbazla Ismail (Brajamusti Publication, 2025)
Online defamation in Malaysia reveals not only legal and technological challenges but also entrenched structural inequalities embedded within Criminal Law enforcement. Marginalized groups particularly individuals with low socio-economic status, minority identities, and limited digital or legal literacy face substantial obstacles in pursuing justice, while those with political or social influence tend to receive disproportionately rapid institutional responses. This study examines how discriminatory patterns emerge within Malaysia’s online defamation framework and evaluates Islamic jurisprudence as a normative alternative capable of shaping a more equitable liability structure. Employing a qualitative doctrinal and socio-legal methodology, the article analyzes statutory provisions, judicial decisions, regulatory instruments governing digital communication, and classical Islamic legal sources, complemented by thematic content analysis. The findings indicate that current liability arrangements, including broad immunities for digital intermediaries, reinforce systemic disadvantages by shifting the burden of proof and pursuit entirely onto victims, thereby privileging corporate actors and technologically empowered offenders. In contrast, Islamic legal principles such as hifz al-‘ird (protection of dignity) and tabayyun (verification) offer a proportional, intent-based, and dignity-centered framework for assigning responsibility. The study ultimately proposes a hybrid reform model integrating contemporary Criminal Law with Islamic jurisprudence to reduce structural discrimination, strengthen victim-centered protections, and enhance substantive justice in the digital environment.